Combination drugs in the treatment of ARVI - I. L. Lazarevich; V. S. Kozlov (Медицинский совет, 2013)
"Teaching and Research Medical Center" Federal State Institution of the Russian Federation Presidential Administration ARVI is a very widespread disease that requires a comprehensive approach to treatment, should be targeted at relieving clinical symptoms and meet current safety requirements to medicines. The market of combination drugs for the treatment of ARVI is represented by a variety of drugs for the symptomatic and pathogenetic therapy. AnviMax is the only drug with additional etiotropic action against viral agent which contains antiviral component rimantadine.